The Microbiome and Alzheimer’s Disease: Potential and Limitations of Prebiotic, Synbiotic, and Probiotic Formulations - Arora, Karan; Green, Miranda; Prakash, Satya (Frontiers in Bioengineering and Biotechnology, 2020)
The Microbiome has generated significant attention for its impact not only on the gastrointestinal tract but also on the enteric and central nervous system via the microbiome gut–brain axis, raising the premise that microbiome modulation may be an effective therapeutic strategy for treating or mitigating many human conditions including neurodegenerative disorders. Alzheimer’s disease is a chronic neurodegenerative disease that interferes with cerebral function by progressively impairing memory, thinking and learning through the continuous depletion of neurons. Although its etiopathogenesis remains uncertain, recent literature endorse the hypothesis that probiotic supplementation, whether consumed as the sole supplement or in a synbiotic combination with prebiotics alters Alzheimer’s Disease-like symptoms and reverses levels of AD biomarkers. Alternatively, a dysfunctional microbiota promotes the onset of AD by inducing chronic gastric and neuroinflammation from its resulting impaired gut epithelial barrier, which further exacerbates AD symptoms and biomarkers in patients. The findings in this review suggest that modulation of the microbiome through prebiotics and probiotics have potential as novel biological therapeutics for Alzheimer’s Disease due to their anti-inflammatory and antioxidant properties, their ability to improve cognition and metabolic activity, as well as their capacity of producing essential metabolites for gut and brain barrier permeability.